Angioedema due to Systemic Isotretinoin Therapy - Pelin Üstüner (Hindawi Limited, 2014)
Angioedema is the swelling of the mucosal membranes as a variant of urticaria induced by hereditary C1 esterase inhibitor enzyme deficiency, certain foods, or drugs. Herein, we report the case of a 23-year-old woman, with mild-moderate acne presenting with widespread facial angioedema on the 2nd day of systemic isotretinoin treatment. The patient had taken no drugs other than isotretinoin in the preceding days and had no known food allergy. Her angioedema was resolved after the isotretinoin was discontinued. We want to draw the attention of dermatologists to this rare adverse allergic effect of isotretinoin which is frequently used in the treatment of acne vulgaris.